1998
DOI: 10.1109/69.729736
|View full text |Cite
|
Sign up to set email alerts
|

Scaling access to heterogeneous data sources with DISCO

Abstract: Abstract| Accessing many data sources aggravates problems for users of heterogeneous distributed databases. Database administrators must deal with fragile mediators, that is, mediators with schemas and views that must be signi cantly changed to incorporate a new data source. When implementing translators of queries from mediators to data sources, database implementors must deal with data sources that do not support all the functionality required by mediators. Application programmers must deal with graceless fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
3

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(70 citation statements)
references
References 30 publications
0
67
0
3
Order By: Relevance
“…However, the set of information tuples in the universe is partitioned over one or more database nodes from a wide range of system topologies, for reasons including autonomy, scalability, availability, performance and security. As in a data integration system [9,10,11], the goal is to exploit several independent information sources as if they were a single source. This enables queries for information, resource and service discovery and collective collaborative functionality that operate on the system as a whole, rather than on a given part of it.…”
Section: How Precisely Can a Local Application Discover Relevant Remomentioning
confidence: 99%
“…However, the set of information tuples in the universe is partitioned over one or more database nodes from a wide range of system topologies, for reasons including autonomy, scalability, availability, performance and security. As in a data integration system [9,10,11], the goal is to exploit several independent information sources as if they were a single source. This enables queries for information, resource and service discovery and collective collaborative functionality that operate on the system as a whole, rather than on a given part of it.…”
Section: How Precisely Can a Local Application Discover Relevant Remomentioning
confidence: 99%
“…As in a data integration system [8][9][10], the goal is to exploit several independent information sources as if they were a single source. This is important for distributed systems in which node topology or deployment model change frequently.…”
Section: Query Scopementioning
confidence: 99%
“…As in a data integration system [8][9][10], the goal is to exploit several independent information sources as if they were a single source. However, in a large distributed database system spanning many administrative domains, the set of information tuples in the universe is partitioned over one or more distributed nodes, for reasons including autonomy, scalability, availability, performance and security.…”
Section: Introductionmentioning
confidence: 99%
“…[7,16,19]) propose centralized query compilation and execution coordination. In [3] it is indicated that a distributed mediation framework is a promising research direction, but to the extent of our knowledge the results in this area are sketchy without experimental support.…”
Section: Related Workmentioning
confidence: 99%
“…In [3] it is indicated that a distributed mediation framework is a promising research direction, but to the extent of our knowledge the results in this area are sketchy without experimental support. The protocols for execution of joins between data in different sources are in most cases based on retrieving the data from the sources and assembling the results in the mediator [16,19]. In the DIOM project [13], a distributed mediator system is presented where the query execution is performed in two phases: subquery execution and result assembly.…”
Section: Related Workmentioning
confidence: 99%